The use of Spanish in oral Portuguese-English Teletandem sessions in the MulTeC corpus: a study in light of the concept of translanguaging - Oliveira, Rosângela Aparecida Dantas de (The ESPecialist, 2024)
This work aims to investigate the roles played by the use of Spanish in English-Portuguese dyads during Teletandem Oral Sessions, asking about its impact on learning opportunities. We analyzed six oral interactions between a Brazilian woman, learner of English, and an American man, learner of Portuguese and Spanish. We developed our analysis by understanding the transit between languages from the point of view of translanguaging (García & Wei, 2014) and Teletandem (TTD) (Telles, 2015) as a modality of Virtual Exchange that brings together the affordances for the development of L2 since it places students in real interaction situations who alternate in the roles of proficient and target language learners (Guichon & Cohen, 2016; Walker, 2017 and 2018; Guichon & Wigham, 2016; Swain, 2006 and Swain & Watanabe, 2012). We also challenge the separation of languages as a principle of TTD. Our findings indicate that the use of Spanish had a positive impact on learning opportunities for both interactants, both from the point of view of the development of the target languages and other skills involved in the construction of meaning, especially in interaction with foreign speakers. Regarding the principle of language separation in TTD, our conclusions are in line with Picoli & Salomão (2020) and Satar et al. (2024) and reiterate the need to relativize it in view of current perspectives on language learning and teaching.